2015
DOI: 10.1371/journal.pone.0121768
|View full text |Cite
|
Sign up to set email alerts
|

Central Melanocortins Regulate the Motivation for Sucrose Reward

Abstract: The role of the melanocortin (MC) system in feeding behavior is well established. Food intake is potently suppressed by central infusion of the MC 3/4 receptor agonist α-melanocyte stimulating hormone (α-MSH), whereas the MC 3/4 receptor inverse-agonist Agouti Related Peptide (AGRP) has the opposite effect. MC receptors are widely expressed in both hypothalamic and extra-hypothalamic brain regions, including nuclei involved in food reward and motivation, such as the nucleus accumbens (NAc) and the ventral tegm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 48 publications
1
33
0
1
Order By: Relevance
“…4). [89][90][91][92][93][94][95] Interestingly, females with ablation of Slc17a6 (vGluT2) specifically in Kiss1 neurons appeared to exhibit a normal ovulatory cycle, an indication that glutamatergic neurotransmission from Kiss1 ARH neurons may not be necessary to support reproductive function. 10 In contrast, complete silencing of Kiss1 ARH neurons in adults 88 produces females with irregular estrus cycles, and the majority of females exhibit persistent diestrus with lower plasma LH levels during diestrus as compared with wild-type controls.…”
Section: Vglut2 Deletion In Kiss1 Neuronsmentioning
confidence: 99%
“…4). [89][90][91][92][93][94][95] Interestingly, females with ablation of Slc17a6 (vGluT2) specifically in Kiss1 neurons appeared to exhibit a normal ovulatory cycle, an indication that glutamatergic neurotransmission from Kiss1 ARH neurons may not be necessary to support reproductive function. 10 In contrast, complete silencing of Kiss1 ARH neurons in adults 88 produces females with irregular estrus cycles, and the majority of females exhibit persistent diestrus with lower plasma LH levels during diestrus as compared with wild-type controls.…”
Section: Vglut2 Deletion In Kiss1 Neuronsmentioning
confidence: 99%
“…Likewise, if the POMC 615 neurons are simultaneously activated by the same sensory evidence, then this has an 616 excitatory effect on the same VTA-DA cells, which together with the AgRP disinhibition, 617 provides a means by which VTA-DA signalling can be anchored to updates of predictions on 618 future energetic wealth (i.e., the consequences of beliefs about the current long-term policy 619 are assigned high precision or confidence). This is corroborated by ex-vivo recordings in 620 which VTA-DA neurons increase baseline firing to injections of γ-MSH (Pandit et al 2015). It 621 should be noted that these findings seem to be at odds with the existing consensus that 622 AgRP neurons acts to increase feeding and reward, and MSH acts to decrease feeding (Yen 623 & Roseberry 2015).…”
Section: Interface Between Reward Prediction Errors and Glycaemic Conmentioning
confidence: 81%
“…We next investigated the identity of CTB‐positive neurons in the Arc that did not express NPY. POMC‐expressing neurons represent another major population of neurons in the Arc, which are a separate from the NPY population, and also project to the VTA (Hahn et al, ; Pandit et al, ). We confirmed that Arc POMC‐immunoreactive neurons project to the VTA, and quantified the Arc POMC projection in the same brains used for NPY tracing (Figure a–c).…”
Section: Resultsmentioning
confidence: 99%
“…We also confirm that Arc POMC neurons project to the VTA (Pandit et al, ). Despite a comparable percentage of VTA‐projecting neurons being NPY and POMC (20–30%), it has to be noted that the absolute number of Arc CTB/POMC neurons is larger than the number of Arc CTB/NPY neurons.…”
Section: Discussionmentioning
confidence: 99%